Mikä on suomalaisille pyhää? Pyhien järjestysten paikannuksia - Kyyrö Jere (Tulevaisuuden tutkimuksen seura ry, 2025)
This article analyses the things that are held sacred by the Finns in the 2000s and 2010s.The article discusses academic theories of the sacred, things held sacred by the Finns in the light of earlier studies, religion as a special form of sacred order, and cultural controversies around the figure of Field Marshal Mannerheim as an exemplary case of tensions between sacred orders. Finally, the article reflects on the possible futures of the sacred orders.